Molecular Genetic Characterization of Patients With Focal Epilepsy Using a Customized Targeted Resequencing Gene Panel - Tsai, Meng-Han; Chan, Chung-Kin; Chang, Ying-Chao; Lin, Chih-Hsiang; Liou, Chia-Wei; Chang, Wen-Neng; Ng, Ching-Ching; Lim, Kheng-Seang; Hwang, Daw-Yang (Frontiers in Neurology, 2018)
Objective: Focal epilepsy is the most common subtype of epilepsies in which the influence of underlying genetic factors is emerging but remains largely uncharacterized. The purpose of this study is to determine the contribution of currently known disease-causing genes in a large cohort (n=593) of common focal non-lesional epilepsy patients. Methods: The customized focal epilepsy gene panel (21 genes) was based on multiplex polymerase chain reaction and sequenced by Illumina MiSeq platform. Results: Eleven variants (1.85%) were considered as pathogenic or likely pathogenic, including seven novel mutations. There were three SCN1A (p.Leu890Pro, p.Arg1636Ter, and p.Met1714Val), three PRRT2 (two p.Arg217Profs*8 and p.Leu298Pro), two CHRNA4 (p.Ser284Leu, p.Ile321Asn), one DEPDC5 (p.Val516Ter), one PCDH19 (p.Asp233Asn) and one SLC2A1 (p.Ser414Ter) variants. Additionally, 16 other rare variants were classified as unknown significance due to inconsistent phenotype or lack of segregation data. Conclusion: Currently known focal epilepsy genes only explained a very small subset of focal epilepsy patients. This indicates that the underlying genetic architecture of focal epilepsies is very heterogeneous and more novel genes are likely to be discovered. Our study highlights the usefulness, challenges and limitations of using the multi-gene panel as a diagnostic test in routine clinical practice in patients with focal epilepsy.